The communications of Mercator, upon the contest between the Earl of Selkirk, and the Hudson's Bay Company, on one side, and the North West Company on the other [electronic resource]. - Ellice, Edward, 1781-1863. (Montreal, Lower Canada : Printed by W.Gray, 1817)
Attributed to Edward Ellice--National Union Catalog pre-1956 imprints. Also issued in French: Les communications de Mercator, sur la conteste entre le comte de Selkirk, et la Compagnie de la Baye d'Hudson, d'une part; et la Compagnie du Nord-Ouest, d'autre part. Electronic reproduction. Mode of access: Internet. 44